Epidemiological profile of traumatic brain injury victims of a general hospital in a brazilian capital - Marinho, Cristiane da Silva Ramos (2017)
In Brazil, the accidents and urban violence, the external causes, build a public health problem that has taken big proportions and transcendence, with a big impact on the population's lives. In the set of injuries resulting from external causes, the Traumatic brain injury (TBI) stands out in terms of magnitude, both among dead and injured, being one of the most frequent injuries. Thus, it is important to know epidemiological profile of traumatic brain injury victims, local characteristics, in order to take more effective prevention actions based on this reality, since the primary causes of TBI can vary according to the people involved. The objective of this study was to know the epidemiological profile of traumatic brain injury victims, the type of causative event and the severity of the trauma. Exploratory, cross-sectional, quantitative and descriptive research, conducted with 372 patients suffering from traumatic brain injury. Data were collected from form itself, semi-structured form, and analyzed using the SPSS 20.0 software. The research had the project approved by the Research Ethics Committee, CAAE 30487514.6.0000.5568. There was a predominance of males, aged 18-30 years. The cause of the most common brain injury was traffic accident with a prevalence of moderate traumatic brain injury. It is necessary to the development of preventive actions as well as the development of public policies that contribute to the reduction of morbidity and mortality from TEC and qualified assistance to victims.